A Different Path: The Global Water Crisis and Rainwater Harvesting - Cain, Nicholas (Consilience, 2014)
The global water crisis is predicted to kill 34 to 76 million people by 2020. Large-scale infrastructure projects can provide water, but construction of these projects has not proven adequate to meet growing populations and, even where feasible, large-scale projects have significant social, economic and environmental impacts. A different path to solving the global water crisis that emphasizes efficiency and sustainable, community- scale projects in addition to centralized infrastructure, has been mapped by a range of scholars and activists. Small scale rainwater harvesting is one sustainable approach that is proving increasingly effective in both rural and urban settings in the developing world. This paper surveys the use of rainwater harvesting in India and draws some lessons for the application of this approach to other regions.